2021
DOI: 10.3390/jcm10040791
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Is a Useful Marker for Predicting Histological Types of Early Gastric Cancer

Abstract: Background: The indications for endoscopic submucosal dissection (ESD) for gastric cancer are based on preoperative histological assessment; however, examination of tissue biopsy is not always reliable as only a limited portion of the lesion can be obtained. The neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) are markers of inflammatory response and are potentially associated with the grade of malignancy in gastric cancer. We aimed to investigate the association between NLR and PLR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Systemic inflammation is associated with changes in blood cells such as increased neutrophils, platelets, and MPV. [9][10][11] PLR is a simple inflammatory marker derived from the complete blood count. Previous studies have shown that the PLR was significantly higher in H. pylori-positive than in H. pylori-negative patients, 7 while other studies have disproved this finding.…”
Section: Resultsmentioning
confidence: 99%
“…Systemic inflammation is associated with changes in blood cells such as increased neutrophils, platelets, and MPV. [9][10][11] PLR is a simple inflammatory marker derived from the complete blood count. Previous studies have shown that the PLR was significantly higher in H. pylori-positive than in H. pylori-negative patients, 7 while other studies have disproved this finding.…”
Section: Resultsmentioning
confidence: 99%
“…[9] On GC patients, significantly higher NLR was observed in undifferentiated adenocarcinoma, compared to differentiated adenocarcinoma. [31] NLR < 4 was correlated and corresponded to significant high rate of successful conversion surgery among stage IV GC. [32] In addition, NLR is valuable marker for predicting the treatment response for oral squamous cell carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we showed that the NLR increased in the acute phase after ESD. The NLR is reported to be a marker of systemic inflammation, tumour stage, and histological type of gastrointestinal carcinoma 20 22 . WBC and neutrophils are regulated by TNF-α, IL-1β, and IL-6.…”
Section: Discussionmentioning
confidence: 99%